2010
DOI: 10.1016/j.cognition.2010.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Can false memories prime problem solutions?

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract Previous research has suggested that false memories can prime performance on related implicit and explicit memory tasks. The present research examined whether false memories can also be used to prime higher order cognitive processes, namely, insight-based problem solving. Participants were asked to solve a number of compound remote associate task (CRAT) problems, half of which had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 26 publications
6
52
0
Order By: Relevance
“…Extending these findings, Howe, Garner, Dewhurst, and Ball (2010a) demonstrated that false memories also prime solutions to more complex tasks, namely, insight-based problem-solving tasks. Using the compound remote associate task (CRAT) initially developed by Mednick (1962), participants were required to generate a single word that linked three presented words (e.g., board/mail/magic where the linking solution word is black).…”
Section: Priming Analogical Problem Solutionsmentioning
confidence: 68%
See 4 more Smart Citations
“…Extending these findings, Howe, Garner, Dewhurst, and Ball (2010a) demonstrated that false memories also prime solutions to more complex tasks, namely, insight-based problem-solving tasks. Using the compound remote associate task (CRAT) initially developed by Mednick (1962), participants were required to generate a single word that linked three presented words (e.g., board/mail/magic where the linking solution word is black).…”
Section: Priming Analogical Problem Solutionsmentioning
confidence: 68%
“…Thus, it is clear that the impact of false memory priming on problem solving tasks is not just restricted to children's and adults' CRAT problems (Howe et al, 2010a(Howe et al, , 2011, but also extends to more complex reasoning tasks such as verbal analogical reasoning. That is, the current contribution is also important because false memory priming of CRAT solutions might be seen as simply representing the priming of distant word associations in a network of such associations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations